KEKUATAN HUKUM PEMBUKTIAN WAARRMERKEN (AKTA DI BAWAH TANGAN YANG DIDAFTARKAN) DI NOTARIS - Tjukup, I Ketut; Siki Layang, I Wayan Bela; Martana, Nyoman A.; Putra, Dewa Nyoman Rai Asmara; Arsha Putra, I Putu Rasmadi; Sari Dewi, I Gusti Agung Tirta; Jayanthi, Ni Made Devi (Acta Comitas : Jurnal Hukum Kenotariatan, 2016)
Notary as a public official the only one authorized to make authentic act of the deeds , agreements and determination required by a general rule or by the concerned desired to be declared in an authentic document , ensure certainty the date, saveing , all along the deed was not also be assigned or excluded to the officer or others . As a public official duties and notary work not only makes authentic act but also to register and certify (waarrmerken) letters under a hand. This research is empirical nature of this research is descriptive. Data studied were the primary data (primary data) and secondary data (Secondary data). Sembung research sites in the village. Data collection techniques are literature research and interview techniques . Non probality Sampling Sampling techniques . Data analysis method is a method of qualitative analysis . Waarmerken deed made under the deed of hand function are made under the hand guarantees about the date and the signatures of the parties concerned on the evidence. Deed under the hand that has obtained waarmerken of Notaries has the force of law under these conditions, the deed under the hand that received waarmerken of notary can assist judges in terms of evidence, due to the recognition of the signature , then the contents of the deed was regarded as the agreement of the parties , because the deed under the hand the truth lies in the signature of the parties to the recognition of the signature by the parties and to those who acknowledge his signature on the letter means he also recognizes the contents of the letter that is above his signature that the certificate is a proof of perfect .
Keywords: Notaries, Waarrmerken, Proof